2017
DOI: 10.1002/gps.4778
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of bilingualism to cognitive decline: The Australian Longitudinal Study of Ageing

Abstract: In this cohort, education rather than bilingualism was a predictor of MMSE score, and being bilingual did not protect from cognitive decline. We conclude that bilingualism is complex, and when it is not the result of greater educational attainment, it does not always protect from cognitive decline. Neuroprotective effects of bilingualism over time may be attributable to the precise patterns of language use but not to bilingualism per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…We thank Wei Xing Noah Toh and colleagues for their interest in our paper on bilingualism and cognitive decline . We agree with the authors who say verbal measures of executive function, which we used in our paper, may bias results against those for whom English is not a first language.…”
supporting
confidence: 73%
“…We thank Wei Xing Noah Toh and colleagues for their interest in our paper on bilingualism and cognitive decline . We agree with the authors who say verbal measures of executive function, which we used in our paper, may bias results against those for whom English is not a first language.…”
supporting
confidence: 73%
“…Mukadam et al analyzed a large‐scale, prospective dataset from the Australian Longitudinal Study of Ageing (ALSA)—which tracked a sample of 2,087 elderly participants (65 years or older) across 20 years—and found that bilinguals and monolinguals did not significantly differ in executive functioning and cognitive decline. The authors conclude that bilingualism “does not protect from cognitive decline or enhance cognitive function.”1(p7) Despite the authors' laudable intentions, we would caution that their conclusions are premature.…”
Section: Summary Of Studies Comparing Monolinguals and Bilinguals On mentioning
confidence: 99%
“…This speaks to the importance of bilinguals' interactional contexts of conversational exchanges, which impose varying levels of control demands on bilinguals . Specifically, bilinguals who reside in a predominantly English‐speaking society (e.g., Australia; Mukadam et al) would resemble single‐language context bilinguals (e.g., speaking English at work and non‐English/native language at home). In contrast, bilinguals who reside in a linguistically diverse environment (e.g., Hyderabad; Alladi et al) would resemble dual‐language context bilinguals who speak multiple languages interchangeably within the same contexts.…”
Section: Summary Of Studies Comparing Monolinguals and Bilinguals On mentioning
confidence: 99%
“… Rossi et al, 2017 ; cf. Kavé et al, 2008 ; Mukadam et al, 2017a , b ; and see Grady et al, 2015 , for a similar proposed mediation model with lifelong use of two languages as predictor, and stronger (neuro) functional connections and greater (neuro) modulation of task-related activity mediating executive control].…”
Section: Moderating and Mediating Effects Of Bilingualismmentioning
confidence: 99%
“…So far, we have reviewed the evidence supporting bilingualism as an expression of cognitive reserve (see also, Bialystok et al, 2014 ; but see Zahodne et al, 2014 ; Mukadam et al, 2017a , b ; Hack et al, 2019 ; Papageorgiou et al, 2019 ), in addition to other factors or predictors involved (e.g., education, IQ, occupation, SES, and immigration status). However, relationships between and among (predictors) factors are complex and might be modified by third variables ( Fairchild and MacKinnon, 2009 ).…”
Section: Moderating and Mediating Effects Of Bilingualismmentioning
confidence: 99%